2012
DOI: 10.1371/journal.pone.0042832
|View full text |Cite
|
Sign up to set email alerts
|

Is the Aligning Prism Measured with the Mallett Unit Correlated with Fusional Vergence Reserves?

Abstract: BackgroundThe Mallett Unit is a clinical test designed to detect the fixation disparity that is most likely to occur in the presence of a decompensated heterophoria. It measures the associated phoria, which is the “aligning prism” needed to nullify the subjective disparity. The technique has gained widespread acceptance within professions such as optometry, for investigating suspected cases of decompensating heterophoria; it is, however, rarely used by orthoptists and ophthalmologists. The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The concept of converting Sheard's criterion into a continuous variable is not new. Conway et al (2012) defined "Sheard's value" as "the fusional reserve opposing the heterophoria to blur point (or, if no blur to break point) divided by the heterophoria" (p. 2). This implies that Sheard's criterion is unmet if the value is below two.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of converting Sheard's criterion into a continuous variable is not new. Conway et al (2012) defined "Sheard's value" as "the fusional reserve opposing the heterophoria to blur point (or, if no blur to break point) divided by the heterophoria" (p. 2). This implies that Sheard's criterion is unmet if the value is below two.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation disparity, which normally represents a fraction of the measured phoria in the same direction, can be corrected with aligning prisms, and the patient will see the effect while watching the Mallet unit. Conway, Thomas, and Subramanian (2012) compared results from this unit with measures of fusional vergence reserves in 500 adults, and found a strong inverse correlation between positive fusional vergence (PFV) and reported (exo) aligning prism from the Mallett unit for near evaluations (40 cm). At near, 299/500 (≈60%) participants required no aligning prism, however, of these, 107/299 (≈36%) complained of visual symptoms, and 89/299 (≈30%) failed to meet Sheard's criterion (see below).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is considerable evidence from application of the Mallett unit [ 47 , 48 ] that an exo subjective fixation disparity in near vision (or a base-in aligning prism required to compensate a subjective fixation disparity) is associated with asthenopic symptoms [ 49 52 ]. A base-in aligning prism at near is associated with reduced fusional vergence reserves in the opposing direction [ 53 ]. Second, studies based on the Mallett-unit showed that an artificially induced fixation disparity (by means of prisms) can reduce binocular acuity [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Binocular vision uses both eyes that move simultaneously due to the extraocular muscles, which control convergence and divergence and are responsible for binocular vision [24,41]. Binocular vision disorders can generate postural adaptations to maintain binocularity and achieve visual comfort.…”
Section: Discussionmentioning
confidence: 99%